Visual Dysfunction in Posterior Cortical Atrophy - Maia da Silva, Mari N.; Millington, Rebecca S.; Bridge, Holly; James-Galton, Merle; Plant, Gordon T. (Frontiers in Neurology, 2017)
Posterior cortical atrophy is a syndromic diagnosis. It is characterised by progressive impairment of higher (cortical) visual function with imaging evidence of degeneration affecting the occipital, parietal and posterior temporal lobes bilaterally. Most caseswill prove to have Alzheimer pathology. The aim of this review is to summarise the development of the concept of this disorder since it was first introduced. A critical discussion of the evolving diagnostic criteria is presented and the differential diagnosis with regard to the underlying pathology is reviewed. Emphasis is given to the visual dysfunction that defines the disorder, and the classical deficits, such as simultanagnosia and visual agnosia, as well as the more recently recognised visual field defects, are reviewed, along with the evidence on their neural correlates. The latest developments on the imaging of PCA are summarised, with special attention to its role on the differential diagnosis with related conditions.